1989-1994 Wenxue huiyi lu - 880-01 Mu, Xin, 1927-2011. (Guilin)
2 cilt (1. c. xv, [5], 505 sayfa, [8] sayfa resim, tıpkıbasım ; 2. c. [6] sayfa, sayfa [507]-1102, [3 sayfa], [7] sayfa resim, portre, tıpkıbasım)